The Problem of Using ICT-Based PAI Learning Media at SMP Al Banna School, Denpasar City - Dwi Yulia Ulfiani; Hakimuddin Salim; Muh. Nur Rochim Maksum (al-Afkar, Journal For Islamic Studies, 2024)
The use of Islamic Religious Education (PAI) learning media based on Information and Communication Technology (ICT) has become the main focus in increasing the effectiveness of the learning process in the digital era. This research aims to identify problems that arise in the application of ICT-based PAI learning media, as well as uncovering potential solutions to improve the quality of its use. This research uses a qualitative method with a descriptive-analytical approach by collecting data through observation, interviews and literature study. The research results show several problems faced in using ICT-based PAI learning media, including teachers' lack of technological understanding and skills, limited student access to technology, and challenges in integrating religious values ​​in a digital context. Solution approaches are proposed to overcome these problems, including intensive training for teachers in integrating technology into the learning process, developing PAI digital content that is in line with the curriculum and religious values, as well as increasing student access to technology through supportive school policies.